19-13p=-17p-5
+5 +5
24-13p=-17p
+13p +13p
24=-4p
/-4 /-4
-6=p
To simplify and solve this equation we must follow PEMDAS.
P=Parentheses
E=Exponents
M=Multiplication (from left to right)
D=Division (from left to right)
A=Addition
S=Substraction
We begin the process.
10^3=1000
10^7=10000000
New equation looks like this:
7.2*1000/1.8*10000000
We then multiply
7.2*1000= 7200
7200/1.8=4000
4000*10000000= 40000000000
<em>So our final answer is 40000000000.</em>
Hope this helps!
P.S. I forgot this was scientific notation and I solved it a different way. But both ways give the same answer. Let me know if you want the other method.
The expression that is equivalent to 14xy – 28x – 36y + 48 is 2[7x(y-2)-6(3y-4)]
<h3>Factorizing expressions</h3>
Factorization is a way of separating the equations into two separate factors.
Given the expression below;
14xy – 28x – 36y + 48
Group
(14xy – 28x) – (36y + 48)
14x(y - 2) - 12(3y-4)
Factor out the value of 2 from both terms
2[7x(y-2)-6(3y-4)]
Hence the expression that is equivalent to 14xy – 28x – 36y + 48 is 2[7x(y-2)-6(3y-4)]
Learn more on factorization here: brainly.com/question/25829061
#SPJ1
Answer:15
Step-by-step explanation:5 and 3 both go into 15
Step-by-step explanation:
You're asking why
![{- 2(x + 3y) = 18} = y = - 3 - \frac{x}{3}](https://tex.z-dn.net/?f=%20%7B-%202%28x%20%2B%203y%29%20%3D%2018%7D%20%3D%20y%20%3D%20%20-%203%20-%20%20%5Cfrac%7Bx%7D%7B3%7D%20)
let's transpose the first equation for y
-2x-6y=18
-6y=18+2x
6y=-18-2x
y=-18/6-2x/6
y=-3-⅓x as required